Characterization of Microstructure and Mechanical Properties of Chromium Carbide Coatings Formed on 100Cr6 and X200Cr12 Steels through Conversion Process - Belhocine, Abdelghani; Allaoui, Omar; Maazouz, Mourad; Benguesmia, Hani (Engineering, Technology & Applied Science Research, 2025)
A number of deposition processes can be utilized to produce transition metal carbide and nitride coatings. The choice of the deposition process is determined by various parameters, such as coating thickness, use of the deposit, adhesion of the deposit to the substrate, and production cost. In this study, hard chromium carbide coatings are prepared through a conversion treatment on 100Cr6 and X200Cr12 steels. This process consists of electrode position of chromium on the surface of 100Cr6 and X200Cr12 steels followed by a diffusion annealing treatment at 1000 °C and 1100 °C for 1 and 2 hours. All the conversion treatments conducted result in a chromium carbide layer formation on the steel surface. The constituting phases of the formed layer depend on the temperature of the diffusion annealing treatment and the duration at this temperature. In addition, the X-Ray Diffraction (XRD) analysis confirms the presence of chromium oxide in addition to chromium carbides. The micro-hardness profile indicates that both samples attain high hardness values, which are more than four times higher than the base substrate hardness. A well-defined transition zone is also observed, offering the highest adhesion between the deposited layers and the substrate. Scratch tests, in addition to micro-hardness values, determine the improved performance of the X200Cr12 steel sample.